Collarinema eutriglae n. sp. (Nematoda: Cystidicolidae), a new gastric parasite of the scorpaeniform fish Eutrigla gurnardus (Osteichthyes: Triglidae) in the North Sea, with remarks on the systematic status of Collarinema Sey, 1970 - Moravec, František; Sobecka, Ewa (Systematic parasitology, 2012)
A new species of parasitic nematode, Collarinema eutriglae n. sp. (Cystidicolidae), is described from the stomach of the marine scorpaeniform fish Eutrigla gurnardus (Linnaeus), the grey gurnard (Triglidae), collected in the North Sea in the vicinity of the Shetland Islands (61°12'N, 00°30'E) during March, 2011. The new species, studied using both light and scanning electron microscopy, is characterised mainly by the structure of the mouth (small pseudolabia with terminal projections, submedian labia and well-developed sublabia not exceeding the labia externally), very small simple deirids, the length of the spicules (405-423 and 117-135 μm) and non-filamented eggs. Collarinema Sey, 1970 is considered a valid genus and an amended diagnosis is provided. Ascarophis collaris Petter, 1970 is transferred to Collarinema as C. collaris (Petter, 1970) n. comb.
Keywords: mikroskopie elektronová rastrovací; Severní moře; Mouth; ryby; Stomach; druhová specificita; Fish Diseases; žaludek; Species Specificity; Animal Structures; nemoci ryb; Animals; nematodózy; Fishes; Nematode Infections; Microscopy, Electron, Scanning; zvířata; hlístice; ústa; North Sea; Nematoda; anatomické struktury zvířat